A rare neurological complication of typhoid fever: Guillain-Barre’ syndrome - Kapoor, Kapil (Medknow Publications & Media Pvt Ltd, 2014)
Guillain-Barre’ syndrome is a rare complication of typhoid fever, and only a few such cases have been reported in the pediatric age group. We report a young boy with blood culture proven typhoid fever that developed this very rare neurological complication quite early in the course of the disease. Following treatment with intravenous antibiotics and intravenous immunoglobulin, he improved.